CONTINUITY AND CONSISTENCY IN BIOLOGY TEACHING (International journal of artificial intelligence, 2025)
This article analyzes existing curricula and teaching-methodical materials, identifies problematic areas in the educational process. Specific recommendations are given on optimizing the structure of the biology course, introducing innovative pedagogical technologies and methods that serve continuous education and the development of students' scientific thinking.